Enhanced isoflurane suppression of excitatory synaptic transmission in the aged rat hippocampus - Ouanounou, Aviv (1998)
1. The effects of the volatile anaesthetic, isoflurane, were investigated on evoked dendritic field excitatory postsynaptic potentials (f.e.p.s.p.) and antidromic and orthodromic population spikes recorded extracellularly in the CA1 cell layer region in the in vitro hippocampal slice taken from young mature (2–3 months) and old (24–27 months) Fisher 344 rats. 2. Isoflurane depressed the f.e.p.s.ps and the orthodromically-evoked population spikes in both old and young hippocampi. However, the magnitude of the anaesthetic-induced depression was greater in slices taken from old rats compared to those taken from young rats during the application of different isoflurane concentrations (0.5–5%). 3. In the presence of the GABA(A) antagonist, bicuculline methiodide (15 μM), isoflurane suppressed the f.e.p.s.ps to the same extent as was observed in the absence of the GABA(A) antagonist. 4. Orthodromically evoked population spikes were suppressed by isoflurane in a manner quantitatively similar to the suppression of the f.e.p.s.ps. However, antidromic population spikes and presynaptic volleys evoked in young and old slices were resistant to anaesthetic action. In addition, paired pulse facilitation ratio of the evoked dendritic f.e.p.s.ps was not affected in both young and old slices during the application of isoflurane. 5. When slices were exposed to low Ca(2+)/high Mg(2+) solution, isoflurane (1 and 3%) depressed the f.e.p.s.ps in aged slices to the same extent as in young slices. 6. The augmented anaesthetic depression of f.e.p.s.ps in old compared to young hippocampi in the absence and presence of bicuculline, and the lack of anaesthetic effects on antidromic population spikes and presynaptic volleys in old and young slices, suggest that the increased sensitivity of anaesthetic actions in old hippocampi is due to age-induced attenuation of synaptic excitation rather than potentiation of synaptic inhibition. Furthermore, elimination of the increased sensitivity of old slices to anaesthetic actions when the slices were perfused with low Ca(2+)/high Mg(2+) medium, which presumably would decrease intracellular [Ca(2+)], suggests that the enhanced anaesthetic effects in aged neurones might be related to increased intraneuronal [Ca(2+)] in the synaptic terminal.